Cultural Content Analysis in the First Textbook of Arabiyyah Baina Yadaik: Cultural Content Analysis in the First Textbook of Arabiyyah Baina Yadaik - Rofida, Hilya; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative descriptive research examines the cultural content analysis within the inaugural volume of